The effects of age and gender and elite levels on perceptual–cognitive skills of adolescent badminton athletes - Wu, Kuo-Cheng; Lee, Yu-Lung; Chen, Shiau-Cheng (Frontiers in Psychology, 2024)
Introduction: This study aimed to examine perceptual-cognitive skills across age, gender and elite levels of badminton adolescent athletes.Methods: A total of 57 badminton athletes divided into junior high school athletes (age = 13.36 ± 1.14 years, females = 22, males = 11) and senior high school athletes (age = 16.25 ± 0.84 years, females = 11, males = 13) were evaluated using a cognitive component skills approach. Elite levels were classified as semi-elite (n=29, score = 3.23) and competitive elite (n = 28, score = 5.84) levels. Each group completed a cognitive test, including an evaluation of their capacity for Corsi block-tapping (CCT) and spatial priming tasks (SPT). Results: No gender effects were found in the perceptual skills of the adolescent players, and the age effect was consistent across gender. For the elite levels, the perceptual-cognitive skills of SPT of reaction time was performed equally in the groups of semi-elite and competitive players, however, in the CCT Span of working-memory (WM), competitive-elite players outperformed semi-elite players.We found that perceptual-cognitive skills of WM play crucial roles in the open-skill sports of badminton. Thus, when developing advanced skills to higher elite levels in adolescent players, perceptual-cognitive skills should be considered.